[3H]UR‐DE257: Development of a Tritium‐Labeled Squaramide‐Type Selective Histamine H2 Receptor Antagonist. Issue 1 (15th October 2014) - Baumeister, Paul; Erdmann, Daniela; Biselli, Sabrina; Kagermeier, Nicole; Elz, Sigurd; Bernhardt, Günther; Buschauer, Armin
Abstract A series of new piperidinomethylphenoxypropylamine‐type histamine H2 receptor (H2R) antagonists with different substituted "urea equivalents" was synthesized and characterized in functional in vitro assays. Based on these data as selection criteria, radiosynthesis of N‐[6‐(3, 4‐dioxo‐2‐3‐[3‐(piperidin‐1‐ylmethyl)phenoxy]propylaminocyclobut‐1‐enylamino)hexyl]‐(2, 3‐3H2)propionic amide ([3H]UR‐DE257) was performed. The radioligand (specific activity: 63 Ci mmol−1) had high affinity for human, rat, and guinea pig H2R (hH2R, Sf9 cells: Kd, saturation binding: 31 nM, kinetic studies: 20 nM). UR‐DE257 revealed high H2R selectivity on membranes of Sf9 cells, expressing the respective hHxR subtype (Ki values: hH1R: >10 000 nM, hH2R: 28 nM, hH3R: 3800 nM, hH4R: >10 000 nM). In spite of insurmountable antagonism, probably due to rebinding of [3H]UR‐DE257 to the H2R (extended residence time), the title compound proved to be a valuable pharmacological tool for the determination of H2R affinities in competition binding assays.